HUBUNGAN USIA MENARCHE DENGAN KEJADIAN MENOPAUSE DI KAMPUNG LAMPUUK KECAMATAN DARUSSALAM ACEH BESAR - Surya Nola; Zuheri Zuheri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Menarche is a state where the young girls experience their first bleeding in the endometrium which occurs at the age of 10 to 16 years old. While menopause is defined as the point in time when menstrual cycles permanently cease due to the natural depletion of ovarian follicles from aging. In the world, Asia becomes the largest number of women who have menopause early symtoms. In Banda Aceh, Indonesia for example, the prevalence of menopause among 100 women with the age ranges from 40 to 65 reaches 43% with the average age of menopause is at 47,3 years old while the age of menarche last for about 12,22 years. Thus, this study aims to investigate the relationship between the age of menarche and menopause incident in Lampuuk Village, Darussalam, Aceh Besar. The study used an analytical survey method with a cross-sectional design. The sample consisted of 43 women who were chosen by using a total sampling technique.Â The data was collected through the questionnaire. Then, the date were analized using the chi-square test. The result showed the significant value of 0,05 was 0.191. Based on the result, it can be said that there is no significant relationship between the two variables is very weak. Therefore, it can be concluded that more women experience menarche at the age of 13 years old compared to women who experience menarche at the age of 13. In addition to that, this study also reveals that more women experience menopause at the age of 45 years old compared to women who get menopause at the age of 45 years old. Therefore, this study suggest that there is no correlation between the age of menarche and menopause. Based on this study, it is hopped the heath center should improve their counseling approach and do a campaign that menopause is a natural procces and not a disease.Keywords: reproduction, puberty, change